2017
DOI: 10.1111/acer.13520
|View full text |Cite
|
Sign up to set email alerts
|

A Single Session of Attentional Bias Modification Reduces Alcohol Craving and Implicit Measures of Alcohol Bias in Young Adult Drinkers

Abstract: Background Attentional bias modification (ABM) techniques for reducing problematic alcohol consumption hold promise as highly-accessible and cost-effective treatment approaches. A growing body of literature has examined ABM as a potentially efficacious intervention for reducing drinking and drinking-related cognitions in alcohol-dependent individuals as well as those at-risk of developing problem drinking habits. Methods The present study tested the effectiveness of a single session of visual probe-based ABM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Research investigating the effects of VPT-AtBM has reported changes in VPT-AtB in the expected direction in young adult drinkers (38), heavy social drinkers (35), heavy drinkers (HD) (10,32,40), and AUD (31). Another study in AUD showed a trend (27), while two studies in AUD (29,30), and one in binge drinkers (36) found no effects.…”
Section: Atbm: Effects On Experimental Tasksmentioning
confidence: 97%
See 1 more Smart Citation
“…Research investigating the effects of VPT-AtBM has reported changes in VPT-AtB in the expected direction in young adult drinkers (38), heavy social drinkers (35), heavy drinkers (HD) (10,32,40), and AUD (31). Another study in AUD showed a trend (27), while two studies in AUD (29,30), and one in binge drinkers (36) found no effects.…”
Section: Atbm: Effects On Experimental Tasksmentioning
confidence: 97%
“…the Stroop (10), the flicker (10, 40), the stimulus response task (10), the implicit association task (30) or the visual search task [32)]. Meanwhile, one study found VPT-AtBM to inflict expected changes in both an implicit association task and an alcohol-specific Stroop task (38). Further, two studies reported an effect of AtBM on alcohol approach inclination as measured by an approach-avoidance test (27) or by eye-movements in a free viewing task (37).…”
Section: Atbm: Effects On Experimental Tasksmentioning
confidence: 99%
“…Several theoretical models of addiction suggest that individuals who drink alcohol demonstrate preferential attention to alcohol-related cues in their environment, at the expense of competing cues (Franken, 2003; Robinson & Berridge, 2001). This preferential attention is often referred to as an “attentional bias.” Meta-analyses have demonstrated a small but robust link between attentional bias and craving (Field, Munafò, & Franken, 2009), and experimental manipulations of attentional bias have directly influenced alcohol consumption/relapse (Field & Eastwood, 2005; Schoenmakers et al, 2010) and craving (Luehring-Jones, Louis, Dennis-Tiwary, & Erblich, 2017) suggesting a possible causal relationship. However, more recently the clinical relevance of attentional bias has been challenged, with suggestions that weak findings are often overinterpreted and “null” findings ignored (Christiansen, Schoenmakers, & Field, 2015).…”
mentioning
confidence: 99%
“…This pilot study reported support for feasibility and acceptability of this approach, as well as small between-group and large within-group effect size reductions in DPW in support of the efficacy of a counter-attitudinal advocacy paradigm for brief alcohol interventions. A third intervention employed attentional bias modification (ABM) training (Luehring-Jones et al, 2017) in which participants’ attention was actively drawn toward a neutral image compared to an alcohol-related image. Relative to sham training, participants who received active training reported reduced alcohol craving and this reduction was fully mediated by reductions in measures of implicit biases toward alcohol.…”
Section: Resultsmentioning
confidence: 99%